2015
DOI: 10.1152/ajpregu.00568.2013
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of renal endocrine function

Abstract: The kidneys are important endocrine organs. They secrete humoral factors, such as calcitriol, erythropoietin, klotho, and renin into the circulation, and therefore, they are essentially involved in the regulation of a variety of processes ranging from bone formation to erythropoiesis. The endocrine functions are established by cells, such as proximal or distal tubular cells, renocortical interstitial cells, or mural cells of afferent arterioles. These endocrine cells are either fixed in number, such as tubular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 184 publications
0
8
0
Order By: Relevance
“…Although in low dose, it can help strengthen bones and prevent dental caries, however, for instance, due to the wide usage of F in industrial processes, accumulating evidence showed that excessive F exposure causes a variety of adverse effects on soft tissues 2 . The kidney is a multifunctional organ that plays a role in the endocrine, excretory, and hematopoietic systems 3, 4 . It plays an important role in maintaining the homeostasis of the body by selectively excreting or retaining various substances on the basis of specific body needs.…”
Section: Introductionmentioning
confidence: 99%
“…Although in low dose, it can help strengthen bones and prevent dental caries, however, for instance, due to the wide usage of F in industrial processes, accumulating evidence showed that excessive F exposure causes a variety of adverse effects on soft tissues 2 . The kidney is a multifunctional organ that plays a role in the endocrine, excretory, and hematopoietic systems 3, 4 . It plays an important role in maintaining the homeostasis of the body by selectively excreting or retaining various substances on the basis of specific body needs.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship of renin-expressing cells to smooth muscle cells (SMC) expressing (acta2) and pericytes expressing (pdgfrb) was analyzed using Tg(ren:LifeAct-RFP, acta2:EGFP) and Tg(ren:LifeAct-RFP, pdgfrb:EGFP) fish, respectively. With an inverse relationship to smooth muscle actin (SMA), mammalian renin expression increases along metanephric afferent arterioles with decreasing distance from the glomerulus (35,36,48,62). In zebrafish, all renin-expressing cells coexpressed acta2:EGFP (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Anaemia in renal insufficiency is multifactorial, but mainly a consequence of decreased erythropoietin production, due to EPO-producing fibroblasts transdifferentiation into myofibroblasts, predominantly collagen-secreting cells (7,20). This occurs under the influence of proinflammatory cytokines, TNFα and TGFβ.…”
Section: Erythropoietin In Renal Anaemia Treatmentmentioning
confidence: 99%
“…Important role here play hypoxia inducible factors 1 and 2 (HIF 1 and 2) which induce erythropoietin gene transcription (1,6). These are ubiquitary enzymes, but HIF 2 is more present in kidney and liver cells, and hence more specific for EPO gene transcription (7,8). Non-HIF pathways that can alter EPO production include kinase C, GATA-2, nuclear factor kappa B (NFB) pathways (7,9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation